Pelatihan Pembuatan Animasi Sederhana Menggunakan Macromedia Flash Untuk Meningkatkan Keterampilan Siswa SMK Karya Utama Tanjungbalai - Andriyani, Suci; Efendi, Zulfan; Latiffani, Chitra (STMIK Royal, 2024)
Abstract: Education plays an important role in quality human civilization to increase human resources globally. This development reflects the close relationship between education, technological innovation and the advancement of knowledge as an integral part of society's social and intellectual evolution. The use of technology-based media is considered to provide significant benefits for both teachers and students in the process of teaching and learning activities. In this context, the education system in vocational schools should explore the potential resources or potential available around the school environment, which are relevant to the demands of the world of work. In an effort to prepare student graduates who are superior and ready to work and are able to compete in the job market, there needs to be preparation in improving the hard skills and soft skills of mature students. This service activity aims to provide assistance and training to Karya Utama Vocational School students through the use of Multimedia Technology as additional skills. The method in this activity applies training and observation to students. As a result of this activity, 85% of students were able to create simple animations using Macromedia Flash software. Keywords: animation; macromedia flash; multimedia; training.